The strategies to promote Sudan’s tourism destinations post COVID-19 pandemic - Musa, Hussein Gibreel; Fatmawati, Indah; Nuryakin, Nuryakin (PRofesi Humas, 2022)
The global pandemic has brought a halt to various economic, business, as well as tourism activities around the world. It also happens in various countries in Africa, including Sudan. Sudan’s tourism has constantly lasted out of all main economic sectors. The tourism business in Sudan provides many jobs, government revenue, and foreign exchange profits. By analyzing all the marketing actions, media regulations, crisis communication techniques, and advertising campaign components, this article aims to identify strategies used by tourism players in Sudan to re-establish a positive tourism destinations image in times of uncertainty, panic, and struggle, as well as to entice international tourists to return to Sudan’s tourist attractions. The study used qualitative content analysis of the media and marketing strategies, global and local tourism reports, and press interviews to integrate practice and theory and followed the multistep approach for transforming place image. The result shows that Sudanese actors used three strategies to restore a good image of Sudanese tourism destinations: new media strategy, available content strategy, and audience-focused strategy. This study demonstrates why this epidemic must be viewed as an opportunity to adapt to a new normal and rebuild the destination’s image for tourism in a new way.